Pengaruh Kehadiran Apoteker terhadap Standar Pelayanan Kefarmasian di Apotek Kabupaten Rokan Hulu - Diana Resky; Dini Mardhiyani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
The standard of pharmaceutical services serves as a benchmark, especially for pharmacists, in providing pharmaceutical care. This study aims to examine the impact of pharmacists' presence on pharmaceutical services. The research uses a cross-sectional method with a questionnaire as the measurement tool, conducted from April to May 2023. The study sample consists of 31 respondents who are pharmaceutical personnel in pharmacies in Rokan Hulu Regency. The results show that the percentage of pharmacist presence in pharmacies in Rokan Hulu Regency is only 43.46%, which is still considered low. A simple linear regression analysis indicates that the coefficient value of pharmacist presence is 53.310. The linear regression coefficient for Rokan Hulu Regency is 0.404. Based on the coefficient of determination test, the pharmacist presence variable (X) has a high influence on the quality of pharmaceutical services (Y), with a contribution of 79%. The F-test results show a value of 18.769 with a significance level of 0.007 (p<0.05), concluding that the pharmacist presence variable significantly affects pharmaceutical services. Moreover, pharmacist presence contributes to improving key service aspects, such as pharmaceutical supply management, drug information services, and patient counseling. Therefore, efforts to increase pharmacist presence in pharmacies are necessary to ensure pharmaceutical services are more optimal and comply with established standards.